2021
DOI: 10.3390/microorganisms9091900
|View full text |Cite
|
Sign up to set email alerts
|

The Many Faces of Enterococcus spp.—Commensal, Probiotic and Opportunistic Pathogen

Abstract: Enterococcus spp. are Gram-positive, facultative, anaerobic cocci, which are found in the intestinal flora and, less frequently, in the vagina or mouth. Enterococcus faecalis and Enterococcus faecium are the most common species found in humans. As commensals, enterococci colonize the digestive system and participate in the modulation of the immune system in humans and animals. For many years reference enterococcal strains have been used as probiotic food additives or have been recommended as supplements for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
129
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(133 citation statements)
references
References 174 publications
(252 reference statements)
0
129
1
3
Order By: Relevance
“…Although all probiotics present immuno-stimulatory action, E. faecalis is a commensal bacterium that is present in significant numbers in the intestinal microbiome. Therefore, the modulation of the immune system in humans and animals is significant and E. faecalis has proven a better competitor compared to lactic acid bacteria regarding intestinal colonization [49]. A healthy homeostasis and beneficial effects on the intestinal tract are naturally and efficiently preserved by the use of commensal bacteria as probiotics, namely Next-Generation Probiotics (NGP) [50].…”
Section: Growth Performancementioning
confidence: 99%
“…Although all probiotics present immuno-stimulatory action, E. faecalis is a commensal bacterium that is present in significant numbers in the intestinal microbiome. Therefore, the modulation of the immune system in humans and animals is significant and E. faecalis has proven a better competitor compared to lactic acid bacteria regarding intestinal colonization [49]. A healthy homeostasis and beneficial effects on the intestinal tract are naturally and efficiently preserved by the use of commensal bacteria as probiotics, namely Next-Generation Probiotics (NGP) [50].…”
Section: Growth Performancementioning
confidence: 99%
“…Iron deprivation did not have detrimental effects on the Enterococcaceae and Burkholderiaceae families, which are low-abundance yet prevalent members of the human gut microbiome and are largely understudied. Most knowledge about the Enterococcaceae focuses on pathogenesis, and specifically on infection by the opportunistic pathogen Enterococcus faecalis (Keogh et al, 2016; Krawczyk et al, 2021; Saillant et al, 2021). Literature on iron responses of the Burkholderiaceae family is almost nonexistent (Hiippala et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Enterococcus faecium is among the most frequent causes of healthcare-associated infections with underlying co-morbidities such as UTIs, intra-abdominal infection, prostatitis, organ transplantation, diabetes, endocarditis [ 1 ]. E. faecium is also reported as the second most prevalent organism involved in bloodstream infections and rank fourth in terms of surgical site infections in the US and European hospitals [ 2 , 3 ]. Cassini et al reported 16,146 instances of vancomycin-resistant enterococcal infections and 1081 related fatalities in Europe in 2015 [ 4 ].…”
Section: Introductionmentioning
confidence: 99%